2021
DOI: 10.3390/ijerph18179136
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Heart Rate Variability of Stress Level Responses to the Properties of Indoor Environmental Colors: A Preliminary Study

Abstract: Color is the most potent stimulating factor affecting human vision, and the environmental color of an indoor space is a spatial component that affects the environmental stress level. As one of the methods of assessing the physiological response of the autonomic nervous system that influences stress, heart rate variability (HRV) has been utilized as a tool for measuring the user’s stress response in color environments. This study aims to identify the effects of the changes of hue, brightness, and saturation in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…Once seated, they were instructed to slowly move their head and freely explore the room for 3 min. This duration is in line with recent studies in the field ( [41,[43][44][45][46][47][48]; table 1). Subsequently, they received instructions on the sustained attention task [67], which they performed for another 3 min, to ensure they were focused at all times.…”
Section: Methodssupporting
confidence: 91%
See 3 more Smart Citations
“…Once seated, they were instructed to slowly move their head and freely explore the room for 3 min. This duration is in line with recent studies in the field ( [41,[43][44][45][46][47][48]; table 1). Subsequently, they received instructions on the sustained attention task [67], which they performed for another 3 min, to ensure they were focused at all times.…”
Section: Methodssupporting
confidence: 91%
“…Overall, running such well-controlled studies is demanding and it requires high investment in terms of money and time. These numerous methodological challenges probably explain why we found few wellcontrolled empirical studies that could inform us on affective changes in response to colour [7,9,[30][31][32][33]35,[37][38][39][40][41][42][43][44][45][46][47][48]. Among these, even fewer studies used physiological measurements and experimentally manipulated and analysed lightness and/or saturation in addition to hue ([7,41,42]; table 1).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been suggested that the sympathetic activation and parasympathetic withdrawal of autonomic nervous functioning during acute stress can be evaluated using HRV parameters (Spellenberg et al, 2020). However, contradictory and inconsistent results have been reported in the relationship between HRV parameters and stress (Oh et al, 2021). It is not, therefore, possible to assert that certain specific HRV parameters represent stress, although some recent studies have pointed to HRV parameters being highly correlated with stress (Kim et al, 2018).…”
Section: Identifying Emotions In Public Spacesmentioning
confidence: 99%